2001
DOI: 10.1161/hc3101.093866
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Comparison of Enoxaparin, a Low-Molecular-Weight Heparin, With Unfractionated Heparin Adjunctive to Recombinant Tissue Plasminogen Activator Thrombolysis and Aspirin

Abstract: Background-Adjunctive unfractionated heparin (UFH) during thrombolytic therapy for acute myocardial infarction (AMI) promotes the speed and magnitude of coronary artery recanalization and reduces reocclusion. Low-molecularweight heparins offer practical and potential pharmacological advantages over UFH in multiple applications but have not been systematically studied as adjuncts to fibrinolysis in AMI. Methods and Results-Four hundred patients undergoing reperfusion therapy with an accelerated recombinant tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 145 publications
(19 citation statements)
references
References 25 publications
0
18
0
1
Order By: Relevance
“…Of all the studies identified, 12 fulfilled criteria for analysis, including 26,831 patients overall [21,22,23,24,25,26,27,28,29,30,31,32]. LMWH evaluated in these studies were dalteparin, enoxaparin and reviparin.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of all the studies identified, 12 fulfilled criteria for analysis, including 26,831 patients overall [21,22,23,24,25,26,27,28,29,30,31,32]. LMWH evaluated in these studies were dalteparin, enoxaparin and reviparin.…”
Section: Resultsmentioning
confidence: 99%
“…Out of the eight trials (9,945 patients) evaluating enoxaparin [24,25,26,27,28,29,30,31], thrombolysis was carried out with streptokinase in three [24, 29, 31], with tenecteplase in another three [26, 27, 30], with alteplase in one [25], and with tenecteplase or streptokinase or anistreplase in another one [28]. In a single study, no anti-platelet therapy with aspirin was given until day 4 [28].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations